Minding the Machine: Languages of Class in Early Industrial America - Zonderman, David A. (Labour / Le Travail, 2006)
The article reviews the book, "Minding the Machine: Languages of Class in Early Industrial America," by Stephen P. Rice.
Keywords: BOOKS – Reviews; Industrial Revolution; MINDING the Machine: Languages of Class in Early Industrial America (Book); Nonfiction; RICE; Stephen P.